Innovations in an Elementary Accounting Program. - Perritt, Roscoe D. (The Accounting Review, 1971)
The article focuses on innovations in an elementary accounting program. The rapid growth of student enrollment at Northern Illinois University has initiated a challenge to the Department of Accounting to provide effective and yet progressive instruction in elementary accounting for a prospective 1,250 students per year. The article summarizes 6 major innovations of the program. Assisting the Director in planning and organization of the Elementary Accounting Program and in the teaching and evaluation of student performance is a staff of 20 carefully selected graduate assistants who are pursuing the MBA or MS in Accountancy. In conjunction with their teaching assistantship, the graduate assistants enroll in Accountancy 539, a three-hour graduate seminar entitled, Improving Instruction in College Business Courses. The seminar commences with a four 4-day, preschool workshop. The workshop includes instruction in the mechanics of the program, objectives of accounting education, the learning process, various teaching methods and aids, techniques of teaching, handling student differences, and demonstrations on the various teaching approaches.